Combining inflammatory miRNA molecules as diagnostic biomarkers for depression: a clinical study - Brás, João Paulo; Pinto, Sara; von Doellinger, Orlando; Prata, Joana; Coelho, Rui; Barbosa, Mário Adolfo; Almeida, Maria Inês; Santos, Susana Gomes (Frontiers in Psychiatry, 2023)
Background: Inflammation has been implicated in core features of depression pathophysiology and treatment resistance. Therefore, new challenges in the discovery of inflammatory mediators implicated in depression have emerged. MicroRNAs (miRNAs) have been found aberrantly expressed in several pathologies, increasing their potential as biomarkers and therapeutical targets. In this study, the aim was to assess the changes and biomarker potential of inflammation-related miRNAs in depression patients.Manual of Mental Disorders, Fifth Edition (DSM-5). 40 healthy controls and 32 depression patients were included in the study. The levels of inflammatory cytokines were measured in plasma, and expression levels of cytokines and inflammation-related miRNAs were evaluated in peripheral blood mononuclear cells (PBMCs).Results: Depression patients were found to have a pro-inflammatory profile in plasma, with significantly higher levels of TNF-α and CCL2 compared with controls. In PBMCs of depression patients, TNF-a and IL-6 expression levels were significantly up and downregulated, respectively. Moreover, miR-342 levels were found upregulated, while miR-146a and miR-155 were significantly downregulated. miR-342 expression levels were positively correlated with TNF-α. Importantly, when analyzed as a diagnostic panel, receiver operating characteristics (ROC) analysis of miR-342, miR-146a, miR-155 in combination, showed to be highly specific and sensitive in distinguishing between depression patients and healthy controls.In summary, these findings suggest that inflammation-related miRNAs are aberrantly expressed in depression patients. Moreover, we show evidences on the potential of the combination of dysregulated miRNAs as a powerful diagnostic tool for depression.